Analisis Faktor yang Berhubungan dengan Kunjungan Antenatal Care (ANC) Remaja Hamil di Wilayah Kerja Puskesmas Kota Kupang - Elfrida Dana Riwoe Rohi; Aloysius Liliweri; Sabina Gero (Jurnal Manajemen Kesehatan Indonesia, 2022)
Background: Adolescence is a period of “ Opportunity Window”, where an appropriate period to inculcate good values, norms in order to avoid so many problems one of which is on reproductive health issues. The purpose of this study to analyze factors associated with teenage pregnancy ANC Regional Health Center in the city of Kupang. Methods: This was an analytic observational study using cross sectional design. The sample in this study amounted to 81 pregnant teenagers. Statistical analysis used were univariate, bivariate analysis using chi square (x2) and multivariate analysis using multiple regression test (multiple regression) with a confidence level α of 0.05. Results: The results showed the most age groups, namely pregnant teens in the late teens (81.75 % ). The results of the bivariate analysis showed a significant relationship between perception and implementation of ANC (p=0.000), family support with the implementation of the ANC (p=0.048), knowledge with the implementation of the ANC (p=0.006), education with the implementation of the ANC (p=0.000), health care providers with the implementation of the ANC (p=0.001), facilities and infrastructure with the implementation of the ANC (0.007) with antenatal care visit of pregnant teen in the working area of public health centre in city of Kupang. Multivariate analysis showed a dominant factor associated with ANC visit where the variable of negative perception will decrease ANC visit by 2.800 times and variable of low education will decrease ANC visit by 5.375 times.Conclusion: The majority of pregnant teens in City Of Kupang were not complete their ANC visit. Therefore, it requires the involvement of all parties in decreasing the number of teenage pregnancies.